Approaches to Managing Autoimmune Cytopenias in Novel Immunological Disorders with Genetic Underpinnings Like Autoimmune Lymphoproliferative Syndrome - Rao, V. Koneti (Frontiers in Pediatrics, 2015)
Autoimmune Lymphoproliferative Syndrome (ALPS) is a rare disorder frequently due to mutations in FAS (TNFRSF6) gene. Unlike most of the self limiting autoimmune cytopenias sporadically seen in childhood, multi lineage cytopenias due to ALPS are often refractory as their inherited genetic defect is not going to go away. Historically more ALPS patients have died due to overwhelming sepsis following splenectomy to manage their chronic cytopenias than due to any other cause, including malignancies. Hence current recommendations underscore the importance of avoiding splenectomy in ALPS, by long-term use of corticosteroid sparing immunosuppressive agents like mycophenolate mofetil and sirolimus. Paradigms learnt from managing ALPS patients in recent years is highlighted here and can be extrapolated to manage refractory cytopenias in patients with as yet undetermined genetic bases for their ailments. It is also desirable to develop international registries for children with rare and complex immune problems associated with chronic multilineage cytopenias in order to elucidate their natural history and long-term comorbidities due to their disease and its treatments.